Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/adfm.200901305
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Contact Formation on n‐Type Silicon: Basic Reactions and Contact Model for Seed‐Layer Contacts

Abstract: Contact formation on n‐type silicon, especially using a high‐temperature process, has been the subject of research for more than 40 years. After its application in microelectronics, n‐type silicon is widely used in silicon solar cells as the emitter layer. The formation of a low ohmic contact grid using an industrially feasible process step is one of the key features required to improve the solar‐cell efficiency. The contact materials, typically deposited in a printing step, have to fulfil several functions: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…21 In addition, Ag particles show minor corrosion characteristics. 16,22 In our study, after we removed metal residues and the glass layer with an alkaline solution, we observed craters of different sizes on the Si substrate surface. The surface profiles of both sides were measured using α-step profilometry (Figure 6a).…”
Section: Resultsmentioning
confidence: 90%
“…21 In addition, Ag particles show minor corrosion characteristics. 16,22 In our study, after we removed metal residues and the glass layer with an alkaline solution, we observed craters of different sizes on the Si substrate surface. The surface profiles of both sides were measured using α-step profilometry (Figure 6a).…”
Section: Resultsmentioning
confidence: 90%
“…22,23) A very thin glass contact layer of about 10 to 100 nm is formed between the Ag front electrode and the semiconductor silicon by a firing process and an ohmic contact is realized. 24,25) For PV modules using EVA as an encapsulant, moisture (H 2 O molecules) diffuses into 26) and reacts with EVA by a hydrolytic reaction, and acetic acid is produced. [27][28][29][30] The acetic acid produced corrodes the glass contact layer, and the ohmic contact property rapidly degrades when the corrosion proceeds to some extent.…”
Section: Lidmentioning
confidence: 99%
“…It is still not clear how does glassy-phase, which is a molten phase of the glass frit, etch or interact with the SiN x ARC? It was reported that the SiN x ARC can be opened during the firing step by a reaction between the PbO (glass) and SiN x (Horteis et al, 2010). In the reaction, lead oxide (PbO) was reduced to lead.…”
Section: Interface Microstructurementioning
confidence: 99%